Monday

April 21, 2014

April 21, 2014

Posted by **mitch** on Monday, September 15, 2008 at 7:34pm.

(y^2+y-6)(3y+1)=0

- math -
**Quidditch**, Monday, September 15, 2008 at 8:08pmCheck the answer for the similar problem you posted. It is solved the same way.

**Related Questions**

math - how would you solve for y in this problem: x=(y^2+3y)^(1/3) would it ...

ALGEBRA 1!PLZ HELP! - Use the Substitution method to solve the system of ...

mATH, ALGEBRA - i need help solving the system by addition. 5x-7y=5 x+3y=1 this ...

bobpursly,.math - Ok, assume it equals zero. 2x + 3y -6=0 subtract 3y from each ...

math - Need help. solve 5 - y/3 for y= -3, 25 - y = 7 3y + 8 = 3, 5 - 3y =7, y/3...

math - how do I solve this problem 2x/2=(6-3y)/2? 2x/2=(6-3y)/2? I solved it for...

drwls, is this correct,math - drawls this is from the previous post is this ...

correction of math - rewrite the equation 2x-3y= -6 as a function of x. My ...

TO DRWLS/MATH HELP PLEASE - How do i solve inequalitites with three variables. I...

DRWLS CAN YOU ANSWER - How do i solve inequalitites with three variables. I ...